Implikasi Pengaturan Tenaga Kerja Asing Dalam Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja Terhadap Eksistensi Tenaga Kerja Lokal - Muhammad Zainuddin; Saartje Sarah Alfons; Ronny Soplantila (Faculty of Law Universitas Pattimura, 2023)
The development of globalization can trigger an outflow and influx of foreign nationals in a country. This is reinforced by the country's investment policy which makes the need to use foreign workers (TKA) very important. The aim of this research is to discuss the impact of implementing foreign worker regulations in the law. No. 6 of 2023 concerning Job Creation on the existence of local workers.This research is normative juridical research carried out using a statutory approach, conceptual approach and case approach. Results of the Research: The latest regulations regarding licensing for the use of foreign workers regulated in the Job Creation Law have experienced a shift from the field of criminal law to the field of administrative law. The legal ratio of the Employment Law is very different from the Employment Cluster Job Creation Law regarding controlling the use of foreign workers in Indonesia. If the presence of the Job Creation Law is to simplify the licensing process for the use of TKA, then the function of the RPTKA should be the same as IMTA, in this case the sanctions for violations of the use of TKA that do not have an RPTKA are the same as the sanctions for violations of TKA that do not have an IMTA, namely criminal sanctions and not administrative sanctions. In terms of policy, the government has removed several regulations that hamper investment progress through deregulating policies on the use of foreign workers and simplifying policies in order to support increased foreign investment in Indonesia. The impact of the deregulation policy on the use of foreign workers on local workers from a policy perspective provides losses to local workers. The deregulation policy on the use of foreign workers does not actually bring in widespread employment opportunities for local workers, on the contrary, this policy actually facilitates and legitimizes the entry of foreign workers into Indonesia.